1994
DOI: 10.1044/1058-0360.0301.45
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Preschool Narrative Skills

Abstract: The assessment of discourse skills in young children is an important responsibility facing clinicians today. Early identification of problems in discourse skills and, more specifically, narrative abilities is especially important for identifying children at risk for later learning and literacy-related difficulties. Despite this, few tools are available for assessing narrative skills in preschoolers. In this article we provide information concerning preschool narrative development in typically developing, North… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
145
0
28

Year Published

2006
2006
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 235 publications
(177 citation statements)
references
References 38 publications
4
145
0
28
Order By: Relevance
“…According to teacher reports and school records, none of the children had repeated a grade or had any sensory, intellectual, language, or learning difficulty. I interviewed each of the children in their school setting with a Spanish translation of the same elicitation procedure used by Peterson and McCabe (1983), the Conversational Map of Narratives of Real Experiences (McCabe & Rollins, 1994). After interviews were tape-recorded and completely transcribed, the four longest narratives of each child were selected for analysis (following McCabe & Rollins, 1994) for a total of 32 narratives.…”
Section: Participants and Proceduresmentioning
confidence: 99%
See 3 more Smart Citations
“…According to teacher reports and school records, none of the children had repeated a grade or had any sensory, intellectual, language, or learning difficulty. I interviewed each of the children in their school setting with a Spanish translation of the same elicitation procedure used by Peterson and McCabe (1983), the Conversational Map of Narratives of Real Experiences (McCabe & Rollins, 1994). After interviews were tape-recorded and completely transcribed, the four longest narratives of each child were selected for analysis (following McCabe & Rollins, 1994) for a total of 32 narratives.…”
Section: Participants and Proceduresmentioning
confidence: 99%
“…Peterson and McCabe's (1983) research has highlighted sequentiality and focus on a single experience as goals that drive the narrative development of these children. These authors and colleagues have identified deviations from a sequential timeline as indicators of still being in an early stage of development for U.S. European American English-speaking children (McCabe & Rollins, 1994;Peterson & McCabe, 1983). In their model for assessing narrative skills, for instance, McCabe and Rollins (1994) identified seven hierarchical stages for U.S. European American Englishspeaking children's narrative development.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Further advances in language skills are observed in the form of increasingly mature narrative skills as children progress through the early school years. The inability to tell a coherent story at school entry is a particularly good predictor of persistent language and reading disability among children with a history of delayed language development as preschoolers (28).…”
Section: Oral Languagementioning
confidence: 99%